Liver allocation: urgency of need or prospect of success? : ethical considerations - Bobbert, Monika; Ganten, Tom M. (Clinical transplantation. Supplement, 2013)
In German legislation and in Eurotransplant's practice of liver allocation, urgency of need is considered as the primary distribution criterion. However, at a certain stage, the “sickest-first” principle is regarded as counterproductive as the performance status of these patients receiving an organ is on average critical and mortality and morbidity after liver transplantation increase. Within the medical transplant community, the criterion of prospect for success is highly accepted. As clinicians having a certain scope in decision-making as “gatekeepers” in regard to which patient gets on the waiting list and at which stage a patient is defined as “not transplantable” and as transplantation centers aspire good success rates, the goal of high prospect for success might become more weighty than intended by legislation and professional guidelines. From an ethical point of view, it is submitted a so-called mediatory approach in between the two extremes “sickest-first” and “fittest-first.” Beyond that, it is argued for further development of a prognostic score for post-operative outcome after liver transplantation - as long as questions of social justice are borne in mind - to support “objective” decision-making.
Gesehen am 27.11.2020